2020
DOI: 10.3390/antiox9030242
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Anthocyanin Profiles and Antioxidant Activity of 12 Genotypes of Mulberry (Morus spp.) Fruits and Their Changes during Processing

Abstract: Mulberry fruits are known as rich sources of anthocyanins and are consumed in syrup form after the addition of sugar and acid; however, there is little information on the anthocyanin composition and antioxidant activity of mulberries of different cultivars and their changes during processing. To address this, the antioxidant activity and anthocyanin composition of 12 cultivar mulberry fruit cultivars were investigated by high-performance liquid chromatography and ultra-high-performance liquid chromatography co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…The utilization of fruit as a natural food colorant is derived from their cyanidin and delphinidin glycoside anthocyanins. They are reddish-purple to purple pigments that possess high FRAP and DPPH antioxidant activities [ 47 , 119 ]. Previously, Natić et al [ 119 ] isolated 14 anthocyanins compounds with a total of 45.42–208.74 mg cyn-3-glu/100 g frozen weight, whereas a more recent study by Kim and Lee [ 47 ] obtained 16 types of anthocyanin with total value of 0.95–28.61 mg/g DW.…”
Section: Functional Ingredients In Food Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of fruit as a natural food colorant is derived from their cyanidin and delphinidin glycoside anthocyanins. They are reddish-purple to purple pigments that possess high FRAP and DPPH antioxidant activities [ 47 , 119 ]. Previously, Natić et al [ 119 ] isolated 14 anthocyanins compounds with a total of 45.42–208.74 mg cyn-3-glu/100 g frozen weight, whereas a more recent study by Kim and Lee [ 47 ] obtained 16 types of anthocyanin with total value of 0.95–28.61 mg/g DW.…”
Section: Functional Ingredients In Food Applicationsmentioning
confidence: 99%
“…They are reddish-purple to purple pigments that possess high FRAP and DPPH antioxidant activities [ 47 , 119 ]. Previously, Natić et al [ 119 ] isolated 14 anthocyanins compounds with a total of 45.42–208.74 mg cyn-3-glu/100 g frozen weight, whereas a more recent study by Kim and Lee [ 47 ] obtained 16 types of anthocyanin with total value of 0.95–28.61 mg/g DW. Among them, cyanidin-3- O -glucoside and cyanidin-3- O -rutinoside were the two significant anthocyanins in M. alba fruit, possessing antioxidant anti-inflammatory properties.…”
Section: Functional Ingredients In Food Applicationsmentioning
confidence: 99%
“…The screening and characterization of polyphenolic compounds showed that some of the polyphenols presented in these seaweeds have strong antioxidant potential. Hydroxycinnamic acid derivatives, hydroxybenzoic acids and their derivatives, protocatechuic acid, anthocyanins, flavonoids and their derivatives, hydroxybenzaldehydes, hydroxytyrosol, phloroglucinol and quercetin derivatives are regarded as potential compounds showing considerable free radical scavenging capacity [66][67][68][69][70][71]. The presence of these antioxidant compounds indicates that seaweeds can be good sources of polyphenols and could be utilized in food, feed, and pharmaceutical industries.…”
Section: Lignansmentioning
confidence: 99%
“…Anthocyanin content was quantified using an Agilent 1260 Infinity II HPLC system (Agilent Technologies) with a diode array detector (DAD) [ 28 ]. Anthocyanin compounds were separated on a Zorbax Eclipse XDB-C 18 column (4.6 × 250 mm, 5 µm; Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%